Correlation of corneal thickness measurements between tono-pachymeter and scheimpflug-placido topography - Ercan, Zeynep Eylül (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Central corneal thickness (CCT) measurements are important for diagnosis,treatment, and surgery planning in ophthalmology. The purpose of this study was to see whether CCT measurements taken with Tono-pachymeter and Scheimpflug-Placido Topography had any significant differences. Tono-pachymeter and topography CCT measurements were taken (n=400). Inter-measurement agreement between them was determined using Bland-Altman Plot analysis. Age groups were also formed as group 1 (aged 18-50 years, 94 males, 106 females) and group 2 (age >51 years, 100 males, 100 females). Mean CCTs measured by Tono-pachymeter and topography were 563.77 +±26.43 and 560.88 + 26.341 microns. Bland-Altman Plot analysis showed in total, 13 were above the upper limit and 5 were under the minimum limit of agreement with regression analysis showing no significant relationships (p=0.213). Group 1 had 7 above and 2 below from the limits of agreement. Group two had 9 above and 2 below from the limits of agreement. Both groups showed insignificant differences between devices (p=0.07 and p=0.86). Tono-pachymeter and Scheimpflug-Placido Topography give reliable CCT results within each other. However, since the limit of agreement ranges can still affect one-to-one patient evaluations, we recommend clinics that use these devices to not interchange measurements in practice.